2001
DOI: 10.1007/s001150170020
|View full text |Cite
|
Sign up to set email alerts
|

Schizophrenie und Gewalttätigkeit

Abstract: The question as to whether schizophrenics have an increased potential for delinquency and violent behavior has given rise to much controversy. During the past few years, a large number of epidemiological studies have demonstrated a moderate but reliable relation between schizophrenic disorders and violence. In the present study, a new approach at investigation was used by evaluating the overall rate of convictions and commitments to psychiatric institutions for general delinquency, violence, and homicide among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 0 publications
0
11
0
2
Order By: Relevance
“…These cases were compared with 1,714,904 individuals in the general population, of whom 27,185 (1.6%) were violent. Publications were from 11 countries: five from the US (874 cases, 4.7% of total number of cases) [42][46]; two from England and Wales ( n  = 66, 0.4%) [27],[47]; two from Denmark ( n  = 1,873, 10.2%) [48],[49]; three from Sweden ( n  = 9,024, 49.0%) [50]–[52]; two from Finland ( n  = 90, 0.5%) reported in three publications [12],[53],[54]; one from Australia ( n  = 2,861, 15.5%) [55]; Germany ( n  = 1,662, 9.0%) [56]; Austria ( n  = 1,325, 7.2%) [57]; Switzerland ( n  = 508, 2.8%) reported in three publications [25],[34],[58]; New Zealand ( n  = 39, 0.2%) [59]; and Israel ( n  = 101, 0.5%) reported in two publications [60],[61]. Violence was ascertained from register-based sources in 13 studies, by self-report and informants in five others, and in two investigations by both methods [43],[59].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These cases were compared with 1,714,904 individuals in the general population, of whom 27,185 (1.6%) were violent. Publications were from 11 countries: five from the US (874 cases, 4.7% of total number of cases) [42][46]; two from England and Wales ( n  = 66, 0.4%) [27],[47]; two from Denmark ( n  = 1,873, 10.2%) [48],[49]; three from Sweden ( n  = 9,024, 49.0%) [50]–[52]; two from Finland ( n  = 90, 0.5%) reported in three publications [12],[53],[54]; one from Australia ( n  = 2,861, 15.5%) [55]; Germany ( n  = 1,662, 9.0%) [56]; Austria ( n  = 1,325, 7.2%) [57]; Switzerland ( n  = 508, 2.8%) reported in three publications [25],[34],[58]; New Zealand ( n  = 39, 0.2%) [59]; and Israel ( n  = 101, 0.5%) reported in two publications [60],[61]. Violence was ascertained from register-based sources in 13 studies, by self-report and informants in five others, and in two investigations by both methods [43],[59].…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies reported risk of violence in mixed samples ( n  = 3,786, 20.6% of all cases) [42][44],[46],[57],[59],[62], which reported an increased risk of violence compared with general population controls. The random-effects pooled OR was 5.0 (3.4–7.4), and the fixed-effects OR was 4.0 (3.4–4.7) with an I 2 of 80% (59%–90%).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, visual deterioration has been associated with the risk for criminal behavior (Bachara and Zaba, 1978; Zinkus and Gottlieb, 1978; Lane, 1980; McKay and Brumback, 1980; Broder et al, 1981; Clack, 1990), one of the strongest indicators of a severe course (Steinert, 1998; Nedopil, 2007; Hutton et al, 2012), outcome (Leygraf, 1988; Haller et al, 2001; Soyka and Morhart-Klute, 2002; Soyka et al, 2002; Fazel et al, 2009; Nitschke et al, 2011; Kooyman et al, 2012), and relapse (Soyka et al, 2004; Witt et al, 2013) in schizophrenia. Specifically, it was argued that in very young children and juveniles, perceptual deficits lead to a higher rate of learning disabilities, specifically reading problems.…”
Section: The Therapeutic Perspective On Schizophreniamentioning
confidence: 99%
“…Über höhere Raten berichteten auch Steadman et al [6] in New York und Sosowsky [7] in Kalifornien. Spätere Arbeiten zeigen ebenfalls, dass das Gewalttätigkeitsrisiko, insbesondere das Risiko für schwerwiegende Aggressionstaten, im Vergleich zur Allgemeinbevölkerung um das 3-bis 10-Fache erhöht ist [8][9][10][11][12][13][14][15][16]. Dieser Faktor ist bei Frauen noch ausgeprägter als bei Männern (15 bis 20), allerdings fallen schizophrene Frauen immer noch viel seltener mit Gewalttaten polizeilich auf als schizophrene Männer [3].…”
Section: Statische Risikofaktorenunclassified